2015
DOI: 10.1186/s12929-015-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the immunophenotypic features of circulating CD4+NKG2D+ T cells in invasive cervical carcinoma

Abstract: BackgroundNKG2D, an activating immunoreceptor, is primarily restricted to NK cells and CD8+ T cells. The existence of an atypical cytotoxic CD4+NKG2D+ T cell population has also been found in patients with autoimmune dysfunctions. Nonetheless, contradictory evidence has categorized this population with a regulatory rather than cytotoxic role in other situations. These confounding data have led to the proposal that two distinct CD4+NKG2D+ T cell subsets might exist. The immune response elicited in cervical canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…CD4-CTLs have to date been almost exclusively associated with late differentiated T EMRA CD4 + cells that accumulate during viral persistence. In this context, several cellular markers have been associated with the development or function of CD4-CTLs, including the transcription factors Eomes (17, 39, 40) and Hobit (11), the surface receptors NKG2D (41, 42) and CX 3 CR1 (17, 43), and the class I–restricted T cell–associated molecule CRTAM (44). We therefore asked whether these markers were similarly expressed by the EBV-specific CD4-CTLs induced by acute infection.…”
Section: Resultsmentioning
confidence: 99%
“…CD4-CTLs have to date been almost exclusively associated with late differentiated T EMRA CD4 + cells that accumulate during viral persistence. In this context, several cellular markers have been associated with the development or function of CD4-CTLs, including the transcription factors Eomes (17, 39, 40) and Hobit (11), the surface receptors NKG2D (41, 42) and CX 3 CR1 (17, 43), and the class I–restricted T cell–associated molecule CRTAM (44). We therefore asked whether these markers were similarly expressed by the EBV-specific CD4-CTLs induced by acute infection.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical intraepithelial neoplasia, a premalignant abnormal growth preceding cervical cancer, is negatively associated with the presence of circulating cytotoxic CD4 T cells (101). Garcia-Chagollan et al identified a population of CD4+ CD28± NKG2D+ T-cells, which appear to be overrepresented in cervical cancer patients and which express the cytotoxic markers CD107a and CD161 (102). While the role of CD4 CTL in protection against tumor formation requires more directed study, the use of immunotherapy and vaccination to induce cytotoxic CD4 responses against tumor antigens is gaining interest, as discussed later in the review.…”
Section: Antigen Recognition By Cd4 Ctl and Possible Targetsmentioning
confidence: 99%
“…Another cytotoxic cell has also been encountered at high numbers in cervical cancer samples [ 109 ]. The expansion of this novel T cell subtype might affect lesion fate [ 110 ].…”
Section: Cytokinesmentioning
confidence: 99%
“…The expansion of this novel T cell subtype might affect lesion fate [ 110 ]. It is positive for CD4 and NKG2D markers and is subdivided in CD28 +/− , showing a statistically significant association with underexpression of several proinflammatory cytokines, such as IL1- β , IL-2, and TNF- α [ 109 ]. The role it plays and whether it is related to tumor growth or tumor suppression are still not known.…”
Section: Cytokinesmentioning
confidence: 99%